IMPACT OF SHOCK ABSORBERS QUALITY ON THE SAFETY OF CAR PASSENGERS AND CARGO - Grinkevičius, Saulius; Tamokaitis, Saulius (PROFESSIONAL STUDIES: Theory And Practice, 2024)
The analysis of impact of properly operating shock absorbers having a substantial influence on the vehicle safety is a main issue of this paper. A "Quarter-car suspension model" has been used in creating mathematic model for dynamic processes analysis – system of differential equations. The dynamic processes taking place in the wheel suspension has been mathematically described using Quarter-car suspension model. A system of differential equations has been created and applied for programming Scilab Xcos. The results of modeling were verified by performing practical performance using automobile Volvo S80. The results of process modeling and practical car braking using shock absorbers of various quality evidently show the importance of their quality and significant impact on vehicle stability on the road. The simulation, applying Scilab X cos system allows to conclude that the mechanical oscillations during the braking process are quite significant (oscillation amplitude from 0.2, 0,1 m through 3 s period). In case of shock absorber malfunctioning the process simulation, when the damping force of the suspension system was 10 times reduced, the amplitude of moving masses grows up about twice and the period of oscillations lasts more than 3,5 times longer. That allows us to predict that these parameters could expand a braking time up to 20% - 30%, thus affecting the wheel's clamping force and, at the same time, the wheel's adhesion to the road. These factors directly affect the length of the braking distance, as well as the stability of the car's movement in the turn. Because, the results of practical measurements, proved the shock absorbers quality influence on so important parameters like vehicle stopping time and distance, quite often defining the vehicle safety on the road it‟s reasonable to stress on the importance of more strict technical quality control of shock absorbers.